PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON KELAS X SMA PGRI PEKANBARU - Mukarramah, Hafizhah Al-Mukarramah Al (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The purpose of this research is to improve student achievement on the subject of Hydrocarbon in class X SMA PGRI Pekanbaru. This research is a form of quasi-experimental study with pretest-posttest design. The population in this study was a high school science class X PGRI Pekanbaru consisting of 5 classes. Of the population has taken two classes of normal and homogeneous sample , which is a class X 5 as an experimental class and the class as a class X.4 control. Experiment class was given by applied direct instruction model, and the control class was given by conventional method. Analysis of data used t-test. Data of research obtained tcount > ttable (3,44 > 1,67). It means that the application of direct instruction can improve student’s achievement on the subject of Hydrocarbon in class X SMA PGRI Pekanbaru by 17,98 %.Keywords : Direct Instruction, Academic Achievement, Hydrocarbon.